An exploratory study on using Slippery-Liquid-Infused-Porous-Surface (SLIPS) for wind turbine icing mitigation. (December 2020) - Ma, Liqun; Zhang, Zichen; Gao, Linyue; Liu, Yang; Hu, Hui
Abstract: An experimental study was conducted to explore the potentials of using a Slippery-Liquid-Infused-Porous-Surface (SLIPS) for wind turbine icing mitigation. The SLIPS was prepared by infusing a lubricant oil into a nanofibrous membrane, which can stick firmly to the surface of a turbine blade model. While the SLIPS was found to effectively suppress impact ice accretion on the blade surface where strong aerodynamic forces are exerted, ice was still found to accrete in the vicinity of the blade stagnation line where aerodynamic forces are at their minimum. A novel hybrid anti-/de-icing strategy to integrate the SLIPS with a minimized leading-edge heating was demonstrated to effectively remove the ice accretion over entire blade surface. An comprehensive experimental study was also performed to evaluate the durability of the SLIPS to resist wearing away of the substrate materials and depletion of the infused lubricant oil due to "rain erosion" effects, in considering its practical usage for wind turbine icing mitigation. It was found that the "rain erosion" effects would induce significant surface wettability degradation, substantial ice adhesion increment and even structural failures to the SLIPS as the duration of the rain erosion testing increases. Highlights: Slippery-Liquid-Infused-Porous-Surface (SLIPS) is explored for wind turbine icing mitigation. SLIPS is applied to coat the surface of a turbine blade model for icing tunnel testing. The effectiveness of the SLIPS to suppress impact icing on the blade surface was evaluated. A novel hybrid strategy was developed to prevent ice accretion from the entire blade surface. The durability of the SLIPS to resist "rain erosion" effects was assessed experimentally.